The use of playing by the nursing staff on palliative care for children with cancer - Vanessa Albuquerque Soares; Liliane Faria da Silva; Emília Gallindo Cursino; Fernanda Garcia Bezerra Goes
This study aimed to describe ways of using play by the nursing staff on palliative care of children with cancer and analyze the facilitators and barriers of the use of playing on this type of care. Qualitative, descriptive research developed on November 2012 with 11 health professionals, in a public hospital of the state of Rio de Janeiro. Semi-structured interviews and thematic analysis of the information were conducted. The use of playing before procedures was highlighted as a facilitator on palliative care. The child's physical condition, one's restriction, resistance of some professionals and the lack of time for developing this activity, made the use of play harder. We concluded that playing enables the child with cancer, in palliative care, a humanized assistance, being fundamental to integrate it on the care for these children.